PENGAJUAN PEMBATALAN PERKAWINAN OLEH KEPALA KUA KECAMATAN KARANGTENGAH KABUPATEN WONOGIRI PERKARA PERKAWINAN DALAM MASA IDDAH HAMIL - Selviyanti, Pratiwi (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Abstract Marriage annulment is a rare occurrence in society. The purpose of this study was to determine the process of submitting a marriage cancellation and to find out the response of the head of KUA Karangtengah District Wonogiri District to the decision of the Wonogiri Religious Court judge. This research includes the type of qualitative field research, data collection techniques carried out by interview and documentation systems. Interviews with the head of the KUA and the head who receives the registration file. Various sources of data obtained when direct observation to KUA Karangtengah District Wonogiri Regency, books, acticles and scientific work. This research uses descriptive analysis technique that is by analyzing the data available at the time of observation. The results of the study stated that in this study the cancellation of the marriage was carried out by the Head of KUA due to a disability in fulfilling the marriage registration requirements or there were women who were temporarily illicit to be married. As for women who are temporarily forbidden to marry, one of them is a woman who is still in the future of another husband, it happened in KUA, Karangtengah Sub-district, Wonogiri District, the Head of KUA married a pregnant woman who was still in the period of another husband. The incident was due to inaccuracy from the KUA when check registration file. The Head of KUA acknowledged that there was an error in immediately submitting a request for cancellation to the Religious Court to get a marriage stipulation and the result was still declared valid by the Religious Court. Keywords: Annulment Marriage; During Pregnancy. Abstrak Pembatalan perkawinan merupakan kejadian yang langka dalam masyarakat. Tujuan penelitian ini untuk mengetahui proses pengajuan pembatalan perkawinan dan umtuk mengetahui tanggapan kepala KUA Kecamatan Karangtengah Kabupaten Wonogiri terhadap hasil putusan hakim Pengadilan Agama Wonogiri. Penelitian ini termasuk jenis penelitian kualitatif lapangan, teknik pengumpulan data dilakukan dengan sistem wawancara dan dokumentasi. Wawancara dengan kepala KUA dan penghulu yang menerima berkas pendaftaran. Berbagai sumber-sumber data yang didapatkan ketika observasi langsung ke KUA Kecamatan Karangtengah Kabupaten Wonogiri, buku-buku, aktikel dan karya ilmiah. Penelitian ini menggunakan teknik analisis dekskriptif yaitu dengan menganilisis data-data yang ada saat observasi. Hasil penelitian menyatakan dalam penelitian ini pembatalan perkawinan dilakukan oleh Kepala KUA karena adanya kecacatan dalam memenuhi syarat pendaftaran perkawinan ataupun ada wanita yang sementara haram untuk dinikahi. Adapun wanita yang sementara haram untuk dinikahi yakni salah satunya wanita yang masih dalam masa iddah suami lain, hal tersebut terjadi di KUA Kecamatan Karangtengah Kabupaten Wonogiri, Kepala KUA menikahkan perempuan hamil yang masih dalam masa iddah suami lain kejadian tersebut atas tidak ketelitian dari pihak KUA saat memeriksa berkas pendaftaran. Kepala KUA mengetahui adanya kesalahan segera mengajukan permohonan pembatalan ke Pengadilan Agama untuk mendapatkan penetapan pernikahan dan hasilnya tetap dinyakatakan sah oleh Pengadilan Agama. Kata Kunci: Pembatalan Perkawinan; Masa Iddah.